Reverse Stock Splits, Institutional Holdings, and Share Value. Issue 1 (2nd December 2014) - Chung, Kee H.; Yang, Sean
<x xml:space="preserve">Abstract</x> We show that both the number of institutional investors and the percentage of shares that are held by institutional investors increase significantly after reverse splits with a presplit price lower than 5 and a target price higher than 5. This effect is larger than for other comparable reverse splits. These results suggest institutional holdings are affected by the prudent‐person rule and reverse splits are used by firms to alleviate this constraint. We also show that an increase in institutional holdings that results from reverse splits is associated with an increase in share price.